A comparison of traditional and non-traditional student teachers study preference and motivation - Hamdan, Abdul Rahim; Abdul Ghafar, Mohamad Najib; T. R., Black (Fakulti Pendidikan, UTM, 2007)
The study was to explore the students' study approach preferences and levels of motivation in teacher training and is there a link to their academic performance. One hundred students involved in this study. Descriptive statistics, t-tests. correlation analysis. and regression analysis are used to analyse the data. Generally. at the 0.05 significance level. the results show that there is a difference between the two groups of students. The results at the 0.10 significance level show that for traditional students. only mathematics has a strong relation with academic performance. However. through step-wise regression. it is identified that mathematics. Malay language. and surface approach were the possible influences. for non-traditional students. the results show that deep approach. surface approach. experience/time away from study and intrinsic motivation have a significant correlation to academic performance. Using stepwise regression. it is interesting to sec that decp approach to study and experience/time away from study were the better predictors. In conclusion. the results show that the two groups were different to each other in their study preferences. motivation and the predictor that might influence their academic performance. The findings will benefits the institutions. educators and the students themselves to help nurture the preparation for high quality and competent teachers.